'The Robots are Coming!': Perennial problems with technological progress. (28th July 2017) - Atkinson, Paul
Abstract: A proliferation of recent media coverage has addressed the latest advances in artificial intelligence. While expressing admiration for its potential, these publications have worried about the negative impact AI could have on the social order. These sentiments are not new. Similar headlines have accompanied articles about computers ever since the first 'Mechanical Brains' appeared. However, archives reveal that experiments in AI have been undertaken for many years, and yet progress has been fairly limited. Yet, no matter how far away true AI might be, concerns about the consequences of technology remain valid. What is it about our relationship with technology that scares us? We appear to be convinced that the technologies we develop will turn out to destroy us. The paper proposes that fundamental changes need to be made in the discourse of technological progress in order for it to be accepted as more of an opportunity than a threat.